Comparison of Electric-dipole Intensity Parameter for a Series of Structurally Related Pr(III) Complexes with Ureas and thioureas in Non-aqueous Media - David Singh, Th.; Sumitra, Ch.; Rajmuhon Singh, N.; Indira Devi, M. (Asian Journal of Chemistry, 2016)
Absorption difference and comparative absorption spectrophotometric studies involving 4f–4f transitions on praseodymium(III) and different ureas–phenyl urea, biphenyl urea, allyl urea, ethylene urea tetramethyl urea and thioureas–phenyl thiourea, biphenyl thiourea, allyl thiourea, ethylene thiourea and tetramethyl thiourea have been carried out in DMF and CH3OH as well as in DMF-CH3OH, DMF-CH3CN, DMF-dioxane, CH3OH-CH3CN and CH3CN-dioxane mixtures. The small chemical and structural differences due to the ligands and solvents are shown to produce significant variation in the intensities of observed 4f–4f absorption bands and their relative perturbation on 4f–4f transition intensities are readily apparent in the Judd-Ofelt electric dipole (Tl, l = 2, 4, 6) parameters determined for these complexes. Some correlations have also been made from the plots of oscillator strengths of different transitions against Tl parameters which represent the relative sensitivities of different 4f–4f transitions.